State-of-the-art in wind turbine control: Trends and challenges. (July 2016) - Njiri, Jackson G.; Söffker, Dirk
Abstract: Wind energy is one of the most rapidly growing renewable sources of energy due to the fact that it has little negative impact on environment. To meet the growing demand, wind turbines are being scaled up both in size and power rating. However, as the size increases, the structural loads of the turbine become more dominant, causing increased fatigue stress on the turbine components which can lead to early failure. Another area of focus in wind energy is lowering production cost to give it a competitive edge over other alternative power sources. From the control point of view, low production cost of wind energy can be achieved by operating the wind turbine at/or near the optimum power efficiency during partial load regime, guaranteeing reliability by reducing fatigue loads, and regulating generated power to its rated value in the high wind regime. Often, it is difficult to realize a control algorithm that can guarantee both efficiency and reliability because these two aspects involve conflicting objectives. This paper reviews various control strategies that are used in wind turbine systems, both in low and high wind speed regions focusing primarily on multi-objective control schemes. Emerging trends that are likely to influence the current or future wind energy production, either positively or negatively, are also discussed.